The Diverse Roots of the 'Secular' in East Pakistan (1947–71) and the Crisis of 'Secularism' in Contemporary Bangladesh. (July 2017) - Hasan, Mubashar
Abstract: This article traces the formation of the secular in Bangladesh during the period of 1947–71. Arguably, this is a period when the idea of a 'secular Bengali nation' as opposed to 'Islamic Pakistani nationalism' was coined in by the political forces to foster imagination of a Bengali root of East Pakistan. This article argues with multiple evidence that particular project of secular Bengali nationalism in the sense of strict separation of religion and politics as opposed to religious nationalism makes little sense in contemporary Bangladesh as major parties here are found to manipulate religious nationalism in a society where simplistic and unenlightened interpretation of religion plays a significant role. This article argues that the idea of secular nationalism had multiple meanings and roots during 1947–71 and by acknowledging diverse roots of secular nationalism, it is possible to make sense of contemporary Bangladesh that is by all secular indicators turned into an intolerant entity but at the same time it is equally important to note that Bangladesh's intolerance is devoid of enlightened application and teaching of Islam.